CORO1C is Associated With Poor Prognosis and Promotes Metastasis Through PI3K/AKT Pathway in Colorectal Cancer - Wang, Zongxia; Jia, Lizhou; sun, Yushu; Li, Chunli; Zhang, Lingli; Wang, Xiangcheng; Chen, Hao (Frontiers in Molecular Biosciences, 2021)
Trophoblast cell surface protein 2 (Trop2) is one of the cancer-related proteins that plays a vital role in biological aggressiveness and poor prognosis of colorectal cancer (CRC). The study of the Trop2 related network is helpful for us to understand the mechanism of tumorigenesis. However, the effects of the related proteins interacting with Trop2 in CRC remain unclear. Here, we found that coronin-like actin-binding protein 1C (CORO1C) could interact with Trop2 and the expression of CORO1C in CRC tissues was higher than that in paracarcinoma tissues. The expression of CORO1C was associated with histological type, lymph node metastasis, distant metastasis, AJCC stage, venous invasion, and perineural invasion. The correlation between CORO1C expression and clinical characteristics was analyzed demonstrating that high CORO1C expression in CRC patients were associated with poor prognosis. Furthermore, CORO1C knockdown could decrease the cell proliferation, colony formation, migration and invasion in vitro and tumor growth in vivo. The underlying mechanisms were predicted by bioinformatics analysis and verified by Western blotting. We found that PI3K/AKT signaling pathway was significantly inhibited by CORO1C knockdown and the tuomr-promoting role of CORO1C was leastwise partly mediated by PI3K/AKT signaling pathway. Thus, CORO1C may be a valuable prognostic biomarker and drug target in CRC patients.